MENERAPKAN INOVASI ARTIFICIAL INTELLIGENCE DI BIDANG KESEHATAN LINGKUNGAN - Edmund Edmund; Nicki Carter; Osei Enoch Aboagye; Reynaldi Arsani Runtu; Bayu Syahputra; Fredian Simanjuntak; Indasari Deu (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2023)
ABSTACT The human population in the world today is increasing rapidly, and as the population increases, the need for technology is also urgently needed to balance it. In today's digital era, technology is indispensable to meet human needs. Among them the application of technology in the field of environmental health. The application of technology in the health sector can be said to be very good, because in recent years, technology has helped scientists and doctors find drugs to treat various diseases. Aspects of human health and illness that all depends on the surrounding environmental factors. So, it is very important for humans to pay more attention to the surrounding environment in order to avoid unwanted diseases. It does not only occur due to natural factors, but also occurs due to factors from ourselves. This refers to the theory and practice of assessment carried out by scientists.